Analisa Harmonisa Transformator Satu Fasa Berbeban Motor Arus Searah Melalui Rectifier Dan Simulasi Filter Pasif Berbasis MATLAB Di Laboratorium Program Studi Teknik Elektro Fakultas Teknik Universitas Kristen Indonesia - Dangin, Helda Oktavianti; Silalahi, Eva Magdalena; Purba, Robinson (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2023)
This study analyzed the harmonics of single-phase transformers loaded with Direct Current Motor (MAS) and rectifier using quantitative method approach. The purpose of this study was to identify the Total Harmonic Distortion (THDi) value in transformers and design passive filters to reduce harmonic levels if they do not meet the standards. The results showed that the measurement results, obtained THDi 31.01% in zero-load transformers, in transformers with MAS load with half-wave rectifiers, THDi by 79.35%, and in MAS load transformers with full-wave rectifiers, THDi by 46.40%, which exceeded IEEE 519-2014 standards. The results of the single tuned LC passive filter simulation showed that the MAS loaded transformer with a half-wave rectifier decreased harmonic level from the THDi value of 79.35% before using the filter, to 1.04% after using the filter and met IEEE 519-2014 standards. The harmonic level of MAS loaded transformer with full wave rectifier, before filtering, THDi 46.40%, but after filtering, THDi 37.98%, still exceeds IEEE 519-2014 standard.